Who benefits? Health equity and the Translational Science Benefits Model - La Manna, Anna; Heidbreder, Julie; Casey, Shannon; Phelps, Kat; LaBrier, Mia; Brossart, Laura; Clark, Ella; Tetteh, Emmanuel; Malone, Sara; Luke, Douglas A.; Combs, Todd (Frontiers in Public Health, 2025)
IntroductionEvaluating the impacts of translational science is crucial for demonstrating the quality, relevance, and societal benefits of research. This paper presents current results of efforts to expand the Translational Science Benefits Model (TSBM), a framework and toolkit originally developed at Washington University in St. Louis with 30 specific, real-world benefits across clinical, community, economic, and policy domains. In response to a growing emphasis on health and social equity, we have refined the TSBM to better address and integrate ideas of fairness and justice.MethodsOur methods included a literature scan to identify health equity gaps in the framework, community listening sessions in St. Louis, MO, and Madison, WI, and thematic analysis to incorporate equity into the TSBM.ResultsThe results introduce new dimensions within the existing TSBM domains that include 10 new benefits, all emphasizing themes of trust, power, and access.DiscussionOur aim is to enhance the relevance and utility of the framework and tools to researchers, practitioners, and those affected by implementations of findings from translational science and research. The integration of equity into the TSBM supports continued growth in the number of users and uses of the framework and toolkit to demonstrate health and social impact.